COMPLEX PHYSICAL TRAINING AS A BASIS FOR THE EFFECTIVENESS OF ADAPTIVE BEHAVIOR OF FUTURE OFFICERS IN EMERGENCY CIRCUMSTANCES - ТАГАЕВ Вадим Исмаилович («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article is devoted to the study of the influence of physical training on the formation of adaptive behavior of future of- ficers in extreme conditions. The need for systematic development of specialized physical qualities that ensure increased resistance of the body to increased psychophysical stress of a professional nature is substantiated. Modern scientific concepts of the concept of extremality are presented and the key features of preparing students for effective function- ing in non-standard situations are analyzed. The importance of an integrated approach, which involves close interaction of disciplines of different cycles, is shown for optimizing the educational process. Particular emphasis is placed on the importance of combining theoretical training with practical activities aimed at forming sustainable competencies and readiness to act in risky situations